بيداغوجيا الإدماج وأهميتها في الطور الأول من التعليم الإبتدائي دراسة تقويمية - تواتي طليبة، سلوى; لخويمس, معمر; قديري, صباح (University of Eloued جامعة الوادي, 2024)
تبنى النظام التربوي الجزائري التدريس بالمقاربة بالكفاءات لمعالجة النقائص المسجلة في المقاربات السابقة, وتطلب ذلك البحث عن الآليات والصيغ لأجرأتها على مستوى الواقع والذي يحتاج إلى بيداغوجيات فعالة ونشطة ومتنوعة ترتكز أولا على الكيف, فوقع الاختيار على إستراتيجية بيداغوجيا الإدماج كوسيلة إجرائية لبناء كفاءات المتعلم عن طريق الوضعيات الإدماجية, التي من أهم مرتكزاتها توظيف المعرفة التي تعطيها المدرسة للمتعلم في مجالات الحياة, فهي تهدف إلى تكوين فرد كفء يُعتمد عليه في المستقبل. ولأهمية هذا الموضوع جاءت هذه الورقة البحثية بعنوان: " بيداغوجيا الإدماج وأهميتها في الطور الأول من التعليم الأبتدائي" والتي من خلالها نهدف إلى معرفة الممارسات الميدانية لبيداغوجيا الإدماج في الطور الأول ابتدائي, ومعيقات تطبيقها. The Algerian educational system adopted teaching through the competency approach to address the shortcomings recorded in previous approaches. This required searching for mechanisms and formulas to implement it at the level of reality, which requires effective, active and diverse pedagogies that are based first on quality. The choice fell on the strategy of integration pedagogy as a procedural means to build the learner’s competencies through situations. Integration, one of the most important foundations of which is employing the knowledge that the school gives to the learner in the areas of life, aims to form a competent individual who can be relied upon in the future. Due to the importance of this topic, this research paper was titled: “Inclusion pedagogy and its importance in the first stage of primary education,” through which we aim to know the field practices of inclusion pedagogy in the first stage of primary education, and the obstacles to its application.
لسانيات عامة
Keywords: الكفاءات ــــ بيداغوجيا الإدماج ــــ التعليم الابتدائي ــــ الوضعية الإدماجية; competencies - integration pedagogy - primary education - inclusion situation.